Cost-effectiveness of a fixed dose combination (polypill) in secondary prevention of cardiovascular diseases in India: Within-trial cost-effectiveness analysis of the UMPIRE trial. (1st July 2018) - Singh, Kavita; Crossan, Catriona; Laba, Tracey-Lea; Roy, Ambuj; Hayes, Alison; Salam, Abdul; Jan, Stephen; Lord, Joanne; Tandon, Nikhil; Rodgers, Anthony; Patel, Anushka; Thom, Simon; et al.
Abstract: Background: TheU se ofM ultidrugP illI nR educing cardiovascularE vents (UMPIRE) trial, showed that access to a cardiovascular polypill (aspirin, statin and two blood pressure lowering drugs) significantly improved adherence, lowered systolic blood pressure (SBP) and low-density lipoprotein cholesterol (LDLc) in patients with or at high risk of cardiovascular disease (CVD). We aimed to analyze the within-trial cost-effectiveness of the polypill strategy versus usual care in India. Methods: Relative effectiveness and costs of polypill versus usual care groups in UMPIRE were estimated from the health sector perspective. Only direct medical costs were considered. The effectiveness of the polypill was reported as a percentage increase in adherence and mean reductions in SBP, and LDL-c, over the 15-month trial period. Healthcare resource utilization and costs were collected for each patient during the trial. Polypill price was constructed using a range of scenarios: 0.06–0.94/day. The cost-effectiveness of the polypill was measured as the additional cost for 10% increase in adherence, and per unit reduction in SBP and LDL-c. Results: Overall, the mean cost per patient was significantly lower with the polypill strategy (−203 per person, (95% CI: −286, −119, p < 0.01). In scenario analyses that varied polypill price assumptions, incremental cost-effectiveness ratios for a polypill strategy ranged between cost-saving to 75 per 10% increase in adherence for polypill price of 0.94 per day. Conclusions: The polypill strategy was cost-saving compared to usual care among patients with or at high risk of CVD in India.